2020
DOI: 10.1097/inf.0000000000002913
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis Evaluated With Transient Elastography in 35 Children With Chronic Hepatitis C Virus Infection

Abstract: Background: The aim of this prospective study was to analyze liver fibrosis in teenagers with chronic hepatitis C (CHC) using noninvasive methods. Methods: Thirty-five patients with CHC, 12–17 years of age (mean 14.2 ± 1.8 years; 22/35, 63% male) were included. Most of them (29/35, 83%) were infected vertically, 21/35 (60%) were treatment-naive, 30/35 (86%) were infected with genotype 1 and 5/35 (14%) were infected with genotype 4 HCV. In all patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The risk of cirrhosis in HCV-infected children and adolescents was estimated at 1 to 2% [ 1 , 2 , 3 , 4 , 5 ]. However, a number of recent observational studies have demonstrated that a higher proportion of pediatric patients than had been previously thought may develop advanced liver disease resulting from HCV infection [ 6 , 7 , 8 ]. Turkova et al demonstrated bridging fibrosis in 41% of their patients by histopathological evaluation with a median age of 10.4 years, and liver stiffness measurement (LSM) over 5.0 kPa in transient elastography (TE) evaluation in 30% of patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of cirrhosis in HCV-infected children and adolescents was estimated at 1 to 2% [ 1 , 2 , 3 , 4 , 5 ]. However, a number of recent observational studies have demonstrated that a higher proportion of pediatric patients than had been previously thought may develop advanced liver disease resulting from HCV infection [ 6 , 7 , 8 ]. Turkova et al demonstrated bridging fibrosis in 41% of their patients by histopathological evaluation with a median age of 10.4 years, and liver stiffness measurement (LSM) over 5.0 kPa in transient elastography (TE) evaluation in 30% of patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few outcomes of DAA treatment in cirrhotic pediatric patients have been reported, and there is scarce and limited data on the influence of these therapies on liver fibrosis [ 9 , 10 ]. We recently reported that among our 35 patients aged 12–17 years qualifying for ledipasvir/sofosbuvir (LDV/SOF) treatment, 11% of cases presented with significant fibrosis (F ≥ 2 on the METAVIR scale), including 9% with cirrhosis [ 6 ]. Thus, in this paper, we aim to present the one-year outcomes after therapy in this specific group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although, histopathological changes in liver tissue are characterized by low inflammatory activity and low stages of fibrosis (unlike in adults), they progress over the time. In case of 2-5% of infected children, they may lead to serious liver damage, including cirrhosis (1.8%) and hepatocellular carcinoma (HCC; rarely encountered, a few case reports) [13,14,19,27,39,42].…”
Section: Mother-to-child Transmission Of Hcv and Probable Gaps In The Screening Strategymentioning
confidence: 99%
“…The risk of cirrhosis in HCV-infected children and adolescents was estimated at 1 to 2% [1][2][3][4][5] . However, a number of recent observational studies have demonstrated that a higher proportion of pediatric patients than had been previously thought may develop advanced liver disease resulting from HCV infection [6][7][8] . Turkova et al demonstrated bridging brosis in 41% of their patients by histopathological evaluation with a median age of 10.4 years, and liver stiffness measurement (LSM) over 5.0 kPa in transient elastography (TE) evaluation in 30% of patients 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few outcomes of DAA treatment in cirrhotic pediatric patients have been reported, and there is scarce and limited data on the in uence of these therapies on liver brosis 9,10 . We recently reported that among our 35 patients aged 12-17 years qualifying for ledipasvir/sofosbuvir (LDV/SOF) treatment, 11% of cases presented Loading [MathJax]/jax/output/CommonHTML/fonts/TeX/fontdata.js with signi cant brosis (F ≥ 2 in METAVIR scale), including 9% with cirrhosis 6 . Thus, in this paper, we aim to present the long-term outcomes of therapy in this speci c group of patients.…”
Section: Introductionmentioning
confidence: 99%